2015
DOI: 10.3892/etm.2015.2542
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin attenuates methotrexate-induced pulmonary injury by targeting oxidative stress

Abstract: Abstract. The aim of the present study was to assess the protective effect of silibinin against methotrexate (MTX)-induced pulmonary toxicity. Rats were divided into four groups (MTX, MTX + silibinin, silibinin and control. MTX was injected intraperitoneally (i.p) into female Wistar rats (10 mg/kg/day for 3 days), which resulted in significant increases in the serum levels of alanine aminotransferase, aspartate aminotransferase and oxidant enzymes, including nitric oxide and myeloperoxidase. Furthermore, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…These results indicated that silibinin suppressed airway inflammation caused by SiONPs exposure. These effects caused by silibinin treatment were supported by previous studies [33,34], wherein silibinin alleviated inflammatory response in radiation-or methotrexate-induced pulmonary injury via suppression of cytokine production.…”
Section: Discussionsupporting
confidence: 72%
“…These results indicated that silibinin suppressed airway inflammation caused by SiONPs exposure. These effects caused by silibinin treatment were supported by previous studies [33,34], wherein silibinin alleviated inflammatory response in radiation-or methotrexate-induced pulmonary injury via suppression of cytokine production.…”
Section: Discussionsupporting
confidence: 72%
“…Methotrexate (MTX) is an antineoplastic drug that may be related to folic acid metabolism (Kalemci et al, ). MTX, which is an antagonist of folic acid, is used as an antimetabolite in cancer chemotherapy, leukemia, mammary gland tumors, osteosarcoma, psoriasis, and autoimmune disorders, inhibiting the synthesis of RNA, thymidylate, proteins, and especially DNA (Ali, Rashid, Nafees, Hasan, & Sultana, ; Gautam et al, ; Kalemci et al, ). MTX causes toxic effects in various organs such as kidneys, livers, and bone marrows (Ulusoy, Öztürk, & Sönmez, ) but the precise mechanism in kidney toxicity by MTX remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The increased rate of inflammatory cell infiltration in pulmonary tissue may be due to mitogen-activated protein kinase (MAPK) and Akt pathways. 24 Quercetin, an antioxidant flavonoid widely distributed in plants, green leafy vegetables and fruits has shown beneficial effects in various diseases. The dissemination of quercetin and its metabolites in rats are well distributed in tissues whereby highest concentration noted in lungs and lowest in brain and spleen.…”
mentioning
confidence: 99%